Canadian International Petroleum Conference 2008
DOI: 10.2118/2008-138
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gravity Drainage in Fractured Porous Media Using Rectangular Macromodels

Abstract: I hereby declare that I am the sole author of this thesis. This is a true copy of the thesis, including any required final revisions, as accepted by my examiners. I understand that my thesis may be made electronically available to the public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(61 citation statements)
references
References 30 publications
5
56
0
Order By: Relevance
“…At a constant pumping rate, ΔH between the two G-L interface positions is observed to remain unchanged during each CGD trial; the same result has been found for FFGD experiments (Zendehboudi et al 2008). One can relate these cases by considering identical experimental prototypes in which the matrix block height is so large that one can neglect the threshold capillary height.…”
Section: Elevation Difference Between G-l Interface Positions Withinsupporting
confidence: 67%
See 4 more Smart Citations
“…At a constant pumping rate, ΔH between the two G-L interface positions is observed to remain unchanged during each CGD trial; the same result has been found for FFGD experiments (Zendehboudi et al 2008). One can relate these cases by considering identical experimental prototypes in which the matrix block height is so large that one can neglect the threshold capillary height.…”
Section: Elevation Difference Between G-l Interface Positions Withinsupporting
confidence: 67%
“…Based on our understanding of the free fall gravity drainage (FFGD) process (Zendehboudi et al 2008) and preliminary tests, the following five parameters influencing the process were specified as variables: fracture aperture, matrix height, matrix permeability, well spacing, and fluid viscosity. The dependent variables are CPR, MPWR, RF, and vertical elevation difference (ΔH) between the G-L interface positions in the matrix and fractures during CGD.…”
Section: Design Of Experimentsmentioning
confidence: 99%
See 3 more Smart Citations